Bead mills in pharmaceutical and biotechnology production - Gubenia, Oleksii; Kasyniuk, Maksym; Hrininh-Hera, Kateryna; Omelianenko, Kostiantyn (My University, 2025)
The cells of mycelial fungi, yeast, unicellular algae and bacteria contain valuable components, for example, proteins, polysaccharides, lipids, enzymes, biodegradable polymers, vitamins, amino acids, and also produce the substances with therapeutic properties. The method of disruption of cells of microorganisms in the bead mills is used mainly for mycelial fungi, yeast and certain types of unicellular algae, with the aim of their further separation into liquid and solid phases and extraction of valuable components.
Keywords: руйнування клітин мікроорганізмів; бісерний млин; cell disruption; bead mill; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра мехатроніки та пакувальної техніки